Teaching functional skills for individual with autism spectrum disorder (ASD): a systematic review - Zulma Indra Rahmi Putri; Nur Azizah; Pujaningsih Pujaningsih (Jurnal Konseling dan Pendidikan, 2023)
Functional skills are an ability needed to navigate everyday daily life. In recent years, many research conducted to improve the functional skills of an individual with autism spectrum disorder (ASD) using a specific intervention. This study investigates articles related to functional skills for an individual with ASD in the database Sage Journal, Scopus, and Springer Link. The selected articles were chosen based on keywords, years of publication and criteria of inclusion. A total of 46 articles were selected to be reviewed in this research. The results showed social skills were researched most among other types of functional skills and video modeling was the most used intervention to improve the functional skills of an individual with ASD. This study provides valuable information on improving functional skills for an individual with ASD and the intervention used to improve it.